ANTIOKSIDAN DALAM MASAKAN MINANG DAN POTENSI PROTEKTIF TERHADAP RISIKO PENYAKIT KARDIOVASKULAR - Helmizar Helmizar; Fasli Djalal; Nur Indrawati Lipoeto (Faculty of Public Health, Andalas University, 2009)
Cardiovascular disease (CVD) is aprimary cause of death in Indoensia nowaday. Development of CVD is caused by some determinant factors, as well as nutrient and non-nutrient intake to result of oxidative stress in the body. Antioxidants, such as vitamin E, beta-caroten, vitamin C andflavonoid, are able to neutralize the effect of free radical from oxidative stress and to influence lipid plasma. The objective of this study was to know the level of antioxidant intake and its association with blood lipid among Minangkabau ethnic. A cross sectional study was conducted in Padang ciry. The study population was adult, age 30 -65 years old, and sampling technique was multistage random sampling, and sample size is 215 respondents. Data collected were demographic characterisitics, food intake using semi quantitative food frequency questionnaire (SMFFQ) and anthropometric measurements. Blood samples were collected to assess plasma lipid profile and level of flavonoid. Data was analyzed with SPSS version 12 and modifiedNutriSurvey Indonesia. The results showed that the average intake of flkaroten was 15.0 ( SD 6. 7) mg/dcry, vitamin C was 66. 3 (SD 30.6) mg/day, vitamin E was 17,8 (SD 11.8) mg/day and flavonoid was 105.0 (SD 48.1) mg/day. The level, offlavonoid from Minang traditional food was highfrom